2017
DOI: 10.1016/j.celrep.2017.11.107
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Targeting and Function of SAPAPs Mediated by Phosphorylation-Dependent Binding to PSD-95 MAGUKs

Abstract: The PSD-95/SAPAP/Shank complex functions as the major scaffold in orchestrating the formation and plasticity of the post-synaptic densities (PSDs). We previously demonstrated that the exquisitely specific SAPAP/Shank interaction is critical for Shank synaptic targeting and Shank-mediated synaptogenesis. Here, we show that the PSD-95/SAPAP interaction, SAPAP synaptic targeting, and SAPAP-mediated synaptogenesis require phosphorylation of the N-terminal repeat sequences of SAPAPs. The atomic structure of the PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…To obtain soluble and well behaving GKAP and Shank3, we removed part of the sequences of the two proteins (see Figure 1A and STAR Methods for details). The binding affinities between PSD-95 and GKAP, between GKAP and Shank3, and between Shank3 and Homer3 were essentially the same as the bindings investigated using the isolated domains as reported previously (Zeng et al, 2016b;Zhu et al, 2017) . We also confirmed that Homer3 is a homo-tetramer (Hayashi et al, 2006(Hayashi et al, , 2009.…”
Section: Psd Condensates Formation By Mixing Major Psd Scaffold Proteinssupporting
confidence: 80%
See 1 more Smart Citation
“…To obtain soluble and well behaving GKAP and Shank3, we removed part of the sequences of the two proteins (see Figure 1A and STAR Methods for details). The binding affinities between PSD-95 and GKAP, between GKAP and Shank3, and between Shank3 and Homer3 were essentially the same as the bindings investigated using the isolated domains as reported previously (Zeng et al, 2016b;Zhu et al, 2017) . We also confirmed that Homer3 is a homo-tetramer (Hayashi et al, 2006(Hayashi et al, , 2009.…”
Section: Psd Condensates Formation By Mixing Major Psd Scaffold Proteinssupporting
confidence: 80%
“…To obtain soluble and well behaving GKAP (aka SAPAP1 or DLGAP1) and Shank3, we removed part of the sequences of the two proteins. Specifically, we removed part of the sequences on GKAP connecting three PSD-95 GK-binding repeats (GBRs) (Kim et al, 1997;Zhu et al, 2017) and a C-terminal extended PDZ-binding motif (PBM) required for stable Shank binding (Zeng et al, 2016b). Shank3 is a very large scaffold protein that is difficult to obtain a highly purified, well behaving full-length recombinant protein.…”
Section: Methods Details Protein Expression and Purificationmentioning
confidence: 99%
“…In 320 order to gain insight into the nature of the binding of Gnb5 to the PSD-95 GK domain, we 321 compared PSD-95 -Gnb5 binding to PSD-95 -GKAP binding. GKAP ('GK'-associated protein, 322 also referred to as SAPAP1 or DLGAP1) is an established synaptic GK domain binder (Kim et 323 al., 1997) whose interaction involves the GMP-binding region (Zhu et al, 2017). These ideas 324 are also validated by our own coimmunoprecipitation experiments: GKAP can be efficiently 325 coprecipitated upon pull-down of either the isolated GK domain or an intact PSG module, 326…”
Section: Psd-95 Interactors Occupy Different Gk Subdomains 313mentioning
confidence: 75%
“…Parallel, a series of clinical imaging studies suggest abnormal synaptic pruning patterns in, among others, frontostriatal brain structures as a possible explanation for volumetric abnormalities in paediatric OCD patients [58,59]. On the other hand, the lower [ 11 C] UCB-J availability in 3-mo old Sapap3 ko mice could also be explained by deviations in synaptogenesis secondary to disruption of the PSD-95/Sapap/Shank complex, with its pivotal role in synaptic development and function [21]. Like Sapap3 ko mice, both PSD-95 ko mice and multiple Shank mutant mouse models show excessive self-grooming and anxiety-like behaviour [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial and the temporal organization of these components plays a central role in synaptic signalling and plasticity [20]. A key aggregate in this structure is the PSD-95/Sapap/Shank complex, which is crucial for synaptic development and transmission [21]. Mice lacking Sapap3 display synaptic dysfunction with aberrant neurotransmission at the level of (cortico)striatal synapses [11,17,[22][23][24][25][26], resulting in a phenotype suggestive for OCD with excessive grooming and increased anxiety-like behaviour.…”
Section: Introductionmentioning
confidence: 99%